두 종류의 스펙트럼영역 빛간섭단층촬영기로 측정한 망막신경섬유층 두께의 비교분석 - 최범석(Beom Seok Choi), 장수경(Su Gyeong Jang), 신종훈(Jong hoon Shin), 이지웅(Ji Woong Lee) (Daihan angwa haghoi jabji, 2016)
목적: 두 종류의 스펙트럼영역 빛간섭단층촬영기(optical coherence tomography, OCT)를 이용하여 측정한 망막신경섬유층 두께의 일치도와 녹내장안 진단의 유용성을 비교하고자 하였다. 대상과 방법: Cirrus OCT와 Spectralis OCT를 이용하여 원발개방각녹내장 환자 56명 89안과 정상인 25명 42안에서 망막신경섬유층 두께를 측정하였다. 두 OCT 기기로 측정한 사분면 및 평균 망막신경섬유층 두께의 일치도를 급내상관계수와 Band-Altman plot을 이용하여 분석하였다. 사분면 및 평균 망막신경섬유층 두께의 녹내장 진단능력 비교는 Area under the receiver operating characteristic curve (AUC)로 분석하였다. 결과: 정상안과 녹내장안에서 두 OCT 기기로 측정한 사분면 및 평균 망막신경섬유층의 두께는 우수한 일치도를 나타내었으나(급내상관계수≥0.81), 이측 사분면에서 Spectralis OCT가 Cirrus OCT보다 더 두껍게 측정되었다(p＜0.001). 두 OCT 기기로 측정한 평균망막신경섬유층 두께가 가장 높은 녹내장 진단력을 보였고(AUC 각각 0.85, 0.87, p=0.30), 사분면 및 평균 망막신경섬유층 두께의 AUC 값은 통계학적으로 유의한 차이가 없었다. 결론: 정상안과 녹내장안 모두에서 Spectralis OCT가 Cirrus OCT보다 이측 망막신경섬유층 두께가 높았으나, 두 기기 간 각 사분영역 및 평균 망막신경섬유층 두께 측정의 일치도는 우수하였고, 녹내장의 진단능력은 차이가 없었다. Purpose: To assess the agreement and compare the performance of glaucoma diagnosis of peripapillary retinal nerve fiber layer (RNFL) thickness measurements between two different spectral-domain optical coherence tomography (SD-OCT) devices. Methods: Eighty nine eyes of 56 patients with glaucoma and 42 eyes of 25 healthy individuals were imaged with Cirrus and Spectralis OCT in a single visit. Agreement between RNFL thickness measurements was assessed using intraclass coefficient (ICC) and Bland-Altman plots. The discriminating abilities of the two techniques for detection of glaucoma were compared by the area under the receiver operating characteristic curves (AUC) for quadrants and average RNFL thickness. Results: ICC values for agreement between both instruments were good for quadrants and average RNFL thickness (all ≥ 0.81). However, Spectralis OCT measurements were significantly greater than Cirrus OCT for temporal quadrant (difference = 4.27 μm in normal group, 3.91 μm in glaucoma group, p < 0.001 for both). The RNFL thickness parameter with the largest AUCs was the average RNFL thickness for the Spectralis OCT and the Cirrus OCT (0.85 vs. 0.87, p = 0.30). The pair-wise comparison among the receiver operating characteristic curves showed no statistical difference for all parameters. Conclusions: Although Spectralis OCT measurements were significantly greater than Cirrus OCT for temporal quadrant, agreement of RNFL measurement between both the devices was generally good and there was no statistically significant difference in the performance of glaucoma diagnosis between both instruments. KCI Citation Count: 1